First Girl Scout : the life of Juliette Gordon Low - Wadsworth, Ginger (Clarion Books, 2012)
Juliette (Daisy) Gordon Low was a remarkable woman with ideas that were ahead of her time. She witnessed important eras in U.S. history, from the Civil War and Reconstruction to westward expansion to post-World War I. And she made history by founding the first national organization to bring girls from all backgrounds into the out-of-doors. Daisy created controversy by encouraging them to prepare not only for traditional homemaking but also for roles as professional women--in the arts, sciences, and business--and for active citizenship outside the home.